Roles of fibrinolytic factors in the alterations in bone marrow hematopoietic stem/progenitor cells during bone repair - Kiyotaka Okada; Minoru Nishioka; Hiroshi Kaji (BMC, 2020)
Abstract In bone tissues, metabolic turnover through bone resorption by osteoclasts and bone formation by osteoblasts, termed bone remodeling, is strictly controlled and maintains homeostasis. Fibrinolytic factors are expressed in osteoclasts and osteoblasts, and are involved in bone remodeling through bone resorption and formation. The repair/regeneration process after bone injury is divided into the acute inflammatory, repair, and remodeling stages. Osteoblasts, osteoclasts, chondrocytes, and macrophages involved in the bone repair process originate from hematopoietic stem/progenitor cells (HSPCs) and mesenchymal stem cells (MSCs) in the bone marrow. Therefore, stem cells in the bone marrow may be strongly influenced by bone injury. The urokinase-type PA (u-PA)/plasminogen (Plg) system functions in macrophage accumulation/phagocytosis through chemokines in the acute inflammatory stage, and Plg increases blood vessel-related growth factor expression, being involved in vascularization in mice. Plasminogen activator inhivitor-1 (PAI-1) causes bone loss and delayed bone repair through the inhibition of osteoblast differentiation in a drug-induced diabetes model in mice. Plg is considered to induce transforming growth factor-β (TGF-β) production in macrophages in the bone repair process, TGF-β release from the extracellular matrix through the activation of matrix metalloproteinase-9 (MMP-9), and stromal cell-derived factor-1 (SDF-1) expression in endosteal preosteoblasts, leading to the induction of bone marrow HSPCs in mice. Based on the above, establishment of a fibrinolytic factor-targeting method efficiently promoting bone repair/regeneration and fracture healing, and development of a new osteoporosis treatment method and diagnostic marker are awaited.